2014
DOI: 10.1007/s00382-014-2122-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of natural climate variability using a weather generator

Abstract: It is common practice to use a 30-year period to derive climatological values, as recommended by the World Meteorological Organization. However this convention relies on important assumptions, of which the validity can be examined by deriving the uncertainty inherent to using a limited time-period for deriving climatological values. In this study a new method, aiming at deriving this uncertainty, has been developed with an application to precipitation for a station in Europe (Westdorpe) and one in Africa (Gulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Empirical mode decomposition (EMD) [Huang et al, 1998] is an algorithm to iteratively extract the intrinsic time scale components from any given series. It has already been applied in studies of climate variability [Brisson et al, 2015;Coughlin and Tung, 2005;Molla et al, 2011;Pegram et al, 2008] and climate effects on plant phenology [Guan, 2014].…”
Section: Interannual Extraction Tools 411 Ensemble Empirical Mode mentioning
confidence: 99%
“…Empirical mode decomposition (EMD) [Huang et al, 1998] is an algorithm to iteratively extract the intrinsic time scale components from any given series. It has already been applied in studies of climate variability [Brisson et al, 2015;Coughlin and Tung, 2005;Molla et al, 2011;Pegram et al, 2008] and climate effects on plant phenology [Guan, 2014].…”
Section: Interannual Extraction Tools 411 Ensemble Empirical Mode mentioning
confidence: 99%
“…Huang et al (1999) demonstrated that EMD is generally successful in retrieving the physically meaningful signals hidden in time series. In some Brisson et al (2015). The significance is defined by the original trend having variability higher than the variability of a trend derived from a randomized time series.…”
Section: Empirical Mode Decomposition (Emd)mentioning
confidence: 99%
“…Observational data of the earth's climate usually cover only several decades, and are thus not long enough to capture this mid-to long-term variability (Hawkins et al 2016). Brisson et al (2015) for example, used a weather generator to quantify uncertainties in estimating climatic conditions from a 30-year period as recommended by the World Meteorological Organization (WMO), and showed that these uncertainties can well exceed 15% for extreme precipitation. This lack of data makes it very difficult or nearly impossible to use observations for the quantification of natural variability on longer time scales.…”
Section: Introduction: Uncertainties In Climate Projectionsmentioning
confidence: 99%